2023
DOI: 10.47895/amp.vi0.7210
|View full text |Cite
|
Sign up to set email alerts
|

Scabies in the Philippines: A Secondary Analysis of Local Patient Registries

Abstract: Background. Scabies is the second most common cause of disability among skin diseases in the Philippines as of 2019. There is no large nationwide study describing the epidemiologic profile of scabies in the country.Objective. This study aimed to describe the demographic, seasonal, and geographic profile of scabies in the Philippines.Methods. We compared secondary data of two local patient registries (Philippine Dermatological Society, PDS, 2010 to 2021; and Philippine Pediatric Society, PPS, 2009 to 2021) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…36 This coincides with the peak months in the previous epidemiological study on scabies from local patient registries. 12 Our findings for clinic-based retrospective chart review (all age groups) studies showed moderate prevalence (4.0 to 6.8%), which is similar to a study included in the systematic review by Khoobdel et al (2023) in a dermatology clinic in Hormozgan, Iran (4.04%). 37 As in our study where prevalence in children in orphanages had high prevalence (39%), institutionalized individuals (i.e., prisoners in Hormozgan, Iran) similarly showed high prevalence: 56.7%.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…36 This coincides with the peak months in the previous epidemiological study on scabies from local patient registries. 12 Our findings for clinic-based retrospective chart review (all age groups) studies showed moderate prevalence (4.0 to 6.8%), which is similar to a study included in the systematic review by Khoobdel et al (2023) in a dermatology clinic in Hormozgan, Iran (4.04%). 37 As in our study where prevalence in children in orphanages had high prevalence (39%), institutionalized individuals (i.e., prisoners in Hormozgan, Iran) similarly showed high prevalence: 56.7%.…”
Section: Discussionsupporting
confidence: 88%
“…There was an earlier publication based on this protocol that reviewed two Philippine medical society patient registries. 12 We included studies that reported on prevalence/ incidence (systematic reviews, cross-sectional studies, cohort studies, case series, studies with clinic/registry/census data) of patients diagnosed with scabies in the Philippines, regardless of setting, age, sex, severity, type, or comorbidity. We excluded narrative reviews, commentaries, and conference proceedings or abstracts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Scabies ranked fourth among new consults with an overall median percentage of 5.15% (IQR 2.35) from 2010-2021 in dermatology training outpatient departments (OPDs) in the Philippines based on the Philippine Dermatological Society Health Information System. 7 The most common first-line of treatment for scabies are topical prescription scabicides such as permethrin 5%, benzyl benzoate 25%, or crotamiton 10%. 8 Most drugs work through a neurotoxic mechanism either by delayed repolarization (permethrin, malathion, lindane) or hyperpolarization (ivermectin) in neuromuscular synapses, thereby paralyzing and killing the mites.…”
Section: Introductionmentioning
confidence: 99%